2007
DOI: 10.1080/01421590701551714
|View full text |Cite
|
Sign up to set email alerts
|

Demographics and motives of medical school applicants in Croatia

Abstract: Background: According to data regarding number of physicians per 100 000 inhabitants, Croatia is below the European average. Under those circumstances, more attention needs to be devoted to Croatian medical schools and their applicants. Aims: This study sought to investigate admission trends of applicants to Croatian medical schools, analyse their demographics and motives for medical school enrollment. Methods: We collected admissions data of applicants to Croatian medical schools from 1979 to 2006. Motives fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
24
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 19 publications
6
24
0
Order By: Relevance
“…The motivation for scientific and educational activities also appeared among the medical students [20]. The motivation for scientific activities is higher among the first-year students, than the final-years students, which are corresponding with our results [21]. We are aware that the interest in controllable lifestyle specialisations showed also an increasing tendency in Croatia.…”
Section: Discussionsupporting
confidence: 78%
“…The motivation for scientific and educational activities also appeared among the medical students [20]. The motivation for scientific activities is higher among the first-year students, than the final-years students, which are corresponding with our results [21]. We are aware that the interest in controllable lifestyle specialisations showed also an increasing tendency in Croatia.…”
Section: Discussionsupporting
confidence: 78%
“…In our recent nation-wide study, applicants to medical schools in Croatia indicated that their choice of a medical school was mostly based on the quality of school and its reputation; however, when we compared in which city they live and what school they choose, it turned out that majority of the respondents chose the geographically closest school [9].…”
Section: Discussionmentioning
confidence: 96%
“…This section would have several purposes as follows: (i) to nurture scientist-citizens who can participate effectively in discussions about issues in science and society; (ii) to increase dialogue between scientists, the public, and policymakers, (iii) to promote multidisciplinary interaction among scholars in our community about complex science policy problems, and (iv) to expand public understanding of science. This section could harbor articles similar to the recent editorial by Petrovečki et al (1) or to the two recently published articles by our group (4,5). When the discussions about science policy are published in a peer-reviewed journal, they assume a higher level of importance and significance.…”
Section: Wanted: Venue For Science Policy Discussionmentioning
confidence: 99%